Quality and storage of pineapple squash as influenced by different sugar and citric acid concentrations - Kanne Sushmitha,; Prahlad Deb,; Gangaram Rana,; Buddhisatya Dowarah, (Annals of Agricultural Research, 2024)
Pineapple squash is one of the most relished processed products and the quantity of sugar and acid in its recipe is yet to be standardized. The present investigation aimed to study the effect of sugar and acid on quality during storage of pineapple squash. The study has been conducted during 2018-2019 at in completely randomized design. For every litre of pineapple juice the treatment wise sugar and acidity requirement were: T1: 2.0kg sugar + 20.0g citric acid, T2: 1.8kg + 17.5g, T3: 1.6kg + 15.0 g, T4: 1.4kg + 12.5g, T5: 1.2kg + 10.0g and T6: 1.0kg + 7.5g. Squash samples of different treatments subjected to biochemical and organoleptic evaluation at monthly interval up to six months. An increasing trend in titrable acidity, reducing sugar was observed while decreasing trend in TSS, total sugar and ascorbic acid was noticed throughout the storage period. T4 was also found to be the best recipe with desirable TSS (44.43 °Brix), titrable acidity (1.90%), reducing sugar (9.52%), total sugar (13.25%), ascorbic acid (7.60 mg/100g) and sugar acid ratio (5.01) including highest sensory score (6.30) for organoleptic qualities like colour, flavour, taste and overall acceptability at 6th month of storage. The present research describes the changes in the quality parameters and organoleptic properties of pineapple squash which reflects the storability of the same.